Combined tracheostomy and maxillomandibular advancement for extremely severe obstructive sleep apnea: A case report - Ning Zhou; Jean-Pierre T.F. Ho; Jan de Lange (Journal of Oral Biology and Craniofacial Research)
Tracheostomy and maxillomandibular advancement (MMA) are both highly effective surgical treatments for adult obstructive sleep apnea (OSA). The present case study described the successful application of combined tracheostomy and MMA for the treatment of extremely severe OSA.